Research competence as a component of professional training of future teachers (Journal of Educational Sciences, 2016)
This article defines the problems of research competencies formation of the future teachers. An analysis of the theoretical research basis allowed to the authors to introduce the concept of “research competence of the teacher” as a characteristic of the personality, that means the possession ofskills and methods of the research in searching knowledge for solving educationalproblems, constructing the whole pedagogical process within the requirements of the modern education. The authors say, there is a strong need for preparing specialists in higher education, who possesses research competencies, as the realities of the society demands creative and thinkingunconventionally specialists, able to find creative decisions of pedagogicalproblems. The article presents the characteristics of scientific, instrumentaland professional research competencies of the future teachers in primaryschool, also it defines the way of their formation, both during the processof giving classes and during the process of all types of pedagogical practiceat school. The main part in formation of research competencies of the futureteachers in primary school, the authors give attention to pedagogical practice, as in the process of organizing the lesson, students make their own investigations in education and educational process of the learners, make diagnosis of intellectual development of pupils, carry out experimentalworks on formation of moral qualities of the child’s personality. It is essential part in the process of research if the students strive to improve the learning process and educational process of pupils.
Keywords: research competence; future teacher scientific-research culture; primary school teacher